2021
DOI: 10.3390/cells10092439
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Transcriptomic Changes of Developing Fetal Brain Reveal Signaling Pathways and Marker Genes of Brain Cells in Domestic Pigs

Abstract: In this study, transcriptomic changes of the developing brain of pig fetuses of both sexes were investigated on gestation days (GD) 45, 60 and 90. Pig fetal brain grows rapidly around GD60. Consequently, gene expression of the fetal brain was distinctly different on GD90 compared to that of GD45 and GD60. In addition, varying numbers of differentially expressed genes (DEGs) were identified in the male brain compared to the female brain during development. The sex of adjacent fetuses also influenced gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 90 publications
3
13
0
Order By: Relevance
“…RNA-seq data analysis was performed as described in our earlier studies. 41,42 Briefly, the quality of raw sequences was checked with FastQC followed by trimming the adaptors from the sequence reads by cutadapt. The fqtrim tool was used to perform base quality trimming (Phred score > 30) by sliding window scan (6 nucleotides).…”
Section: Rna-seq Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-seq data analysis was performed as described in our earlier studies. 41,42 Briefly, the quality of raw sequences was checked with FastQC followed by trimming the adaptors from the sequence reads by cutadapt. The fqtrim tool was used to perform base quality trimming (Phred score > 30) by sliding window scan (6 nucleotides).…”
Section: Rna-seq Data Analysismentioning
confidence: 99%
“…41 We also showed that specific genes are regulated in a sex-bias manner during fetal brain development in pigs. 42 Furthermore, studies by others have shown that epigenetic and metabolic changes in the fetal brain can impact overall health later in life, 34,35 particularly in the context of declining metabolism in the brain. 36,37 However, the epigenetic connection between the development and aging of the brain remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also found evidences for differential expression of specific aging genes in the male and female fetal brain in response to ablation of uterine Foxa2 , an essential gene required for pregnancy establishment (37). We also showed that specific genes are regulated in a sex-bias manner during fetal brain development in pigs (38). Furthermore, studies by others have shown that epigenetic and metabolic changes in the fetal brain can impact overall health later in life (34, 35) particularly in the context of declining metabolism in the brain (36, 37).…”
Section: Introductionmentioning
confidence: 66%
“…RNA-seq data analysis was performed as described in our earlier studies (37, 38). Briefly, the quality of raw sequences was checked with FastQC followed by trimming the adaptors from the sequence reads by cutadapt .…”
Section: Methodsmentioning
confidence: 99%
“…Each library was sequenced to 20 million paired end reads of 150 bases using a NovaSeq sequencer. RNA-seq data analysis was performed as described in our earlier works (108, 120). Briefly, the quality of raw sequences was checked with FastQC followed by trimming the adaptors from the sequence reads by cutadapt .…”
Section: Methodsmentioning
confidence: 99%